2017
DOI: 10.1149/2.0161710jes
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration, Overpotential and Ageing Effects on Cathodes for Solid Oxide Fuel Cells: La0.6Sr0.4Co0.2Fe0.8O3-δversus Ba0.5Sr0.5Co0.8Fe0.2O3-δ

Abstract: The two half-cell systems were compared to evaluate the influence of infiltration, overpotential and ageing on their performance and stability. Structure, microstructure and chemical composition were investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM) coupled with Energy Dispersive X-ray spectroscopy (EDX), whereas redox behavior was evaluated through temperature programmed reduction (TPR) and thermal gravimetric analysis (TGA) in combination with electrochemical impedance spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 90 publications
(169 reference statements)
3
26
0
Order By: Relevance
“…The use of the two fuels allowed achieving high reducing power and high interaction of the fuel mixture with metal cations, favoring the stabilization of Co 2+ reduced state in Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ structure. The obtained oxygen vacancy-rich configuration positively affected oxygen mobility and cathodic performance [22,24].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the two fuels allowed achieving high reducing power and high interaction of the fuel mixture with metal cations, favoring the stabilization of Co 2+ reduced state in Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ structure. The obtained oxygen vacancy-rich configuration positively affected oxygen mobility and cathodic performance [22,24].…”
mentioning
confidence: 99%
“…It has been found that the variation of its molecular weight (MW) can modulate the microstructure and porosity development of the produced material [16,[18][19][20].The mixed-fuels approach in SCS was demonstrated to positively affect the electrocatalytic performance of perovskite-type materials in the oxygen reduction up to an order of magnitude [5,[21][22][23]. PEG (MW = 20,000) was already employed in the compresence of sucrose in two previous papers dealing with Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ powders as cathodes for solid oxide fuel cells prepared by SCS [22,24]. Optimal features and electrochemical properties were reached by a mixture of sucrose and PEG in a 1:2.5 molar ratio [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After calcination at 950 • C, the abovementioned mixture was completely converted into the cubic (Pm-3m) perovskite phase (ICDD, 109462). More details are reported elsewhere [28,30].…”
Section: Resultsmentioning
confidence: 99%
“…The capacitances obtained for the MF and LF semicircles belong to the range 0.42-0.63 mF cm -2 and 85-302 mF cm -2 , respectively. These values indicate that MF and LF semicircles represent oxygen reduction reaction processes [40,41]. The polarisation resistance R p was calculated as the sum of R 2 and R 3 .…”
Section: Resultsmentioning
confidence: 99%